An analysis of the factors affecting the saving habits of university preparatory students / Siti Khadijah Omar ... [et al.] - Omar, Siti Khadijah; Mokhtar, Marziah; Arshad, Azlin Shafinaz; Bakri, Adlan Ahmad; Wan Chek, Wan Ahmad Khusiari; Nik Jaafar, Nik Fazlin Hiryati; Husin, Azira (2018)
Financial management, parental socialization, peer influence and self-control have been acknowledged as determinants of saving behaviour. The aim of this paper is to explore the saving behaviours among students who had just entered their pre-university studies. A stratified random sampling was adopted, and survey questionnaires were distributed to students at the Centre of Foundation studies, Universiti Teknologi MARA, Dengkil Campus. A total of 193 students returned the survey resulting in a response rate of 78.33%. The study reveals that all four determinants of saving behaviours have a significant relationship with saving behaviour where three determinants; financial management, parental socialization and peer influence demonstrated a positive relationship while self-control showed a negative relationship.